2009
DOI: 10.1161/strokeaha.108.522193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Better Adherence to Antihypertensive Agents on Cerebrovascular Disease for Primary Prevention

Abstract: Background and Purpose-The benefits of antihypertensive (AH) drugs on the risks of major cardiovascular outcomes have been demonstrated in clinical trials. However, approximately half of hypertensive patients do not adhere well to their prescribed AH therapy in actual practice. The purpose of this study was to assess the impact of adherence to AH agents on the incidence of cerebrovascular disease (CD) in real-world practice. Methods-A cohort of 83 267 hypertensive patients was reconstructed from the Régie de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 26 publications
3
91
0
5
Order By: Relevance
“…The impact of adherence to hypertensive treatment on health care resources utilisation and/or health outcomes were confirmed by observational studies [23,24] as well as simulation studies [30,31].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The impact of adherence to hypertensive treatment on health care resources utilisation and/or health outcomes were confirmed by observational studies [23,24] as well as simulation studies [30,31].…”
Section: Discussionmentioning
confidence: 79%
“…Available information indicating the impact of SPC treatment on the risk of CVD events [6,7] or indicating a difference in that risk between patients adherent and non-adherent to hypertensive treatment [23,24] applies only to specific groups of patients and cannot be generalised to the total population of patients with arterial hypertension. We used SBP as the only predictor of different health outcomes between patients treated with SPCs and FCs mainly because results of the Framingham Heart Study, which indicated a higher prediction capability of this measure than diastolic blood pressure when assessing both as a continuous variables [14], and to create a framework for the assessment of SPCs in specific subgroups of patients with arterial hypertension (the algorithms used in our study could be easily incorporated in future simulations that could assess the value of SPCs in subgroups of patients).…”
Section: Determinants Of Effectivenessmentioning
confidence: 99%
“…Existing publication focus generally on single cohort of patients [8,16,[18][19][20][21]. We have chosen to compare different cohorts of hypertensive patients managed in the same geographical, clinical and organizational setting in order to have a comprehensive evaluation of the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were grouped into 4 adherence categories as follows: PDC ≤ 40%, ranging from 41% to 60%, ranging from 61% to 80%, and PDC > 80%. When PDC was ≤20%, indication for AHD was considered uncertain or questionable and, therefore, the corresponding subjects were excluded [16].…”
Section: Adherence To Ahtmentioning
confidence: 99%
“…15 A Canadian study reported a 22% reduction in stroke incidence in patients with high adherence (medication possession ratio $80%) compared with patients with lower adherence in a cohort of 83,267 newly treated hypertensive patients. 22 More recently, an Italian populationbased prospective cohort study of 242,594 patients showed a significant increase in the incidence in coronary and cerebrovascular events in patients who discontinued treatment and in patients with low drug coverage, after a mean follow-up of 6 years. 23 The impact of adherence on blood pressure control has been challenged.…”
Section: Consequences Of Poor Adherencementioning
confidence: 99%